IL-10 is significantly involved in HSP70-regulation of experimental subretinal fibrosis. - Yang Yang; Atsunobu Takeda; Takeru Yoshimura; Yuji Oshima; Koh-Hei Sonoda; Tatsuro Ishibashi (PLoS ONE, 2013)
Subretinal fibrosis is directly related to severe visual loss, especially if occurs in the macula, and is frequently observed in advanced age-related macular degeneration and other refractory eye disorders such as diabetic retinopathy and uveitis. In this study, we analyzed the immunosuppressive mechanism of subretinal fibrosis using the novel animal model recently demonstrated. Both TLR2 and TLR4 deficient mice showed significant enlargement of subretinal fibrotic area as compared with wild-type mice. A single intraocular administration of heat shock protein 70 (HSP70), which is an endogenous ligand for TLR2 and TLR4, inhibited subretinal fibrosis in wild-type mice but not in TLR2 and TLR4-deficient mice. Additionally, HSP70 induced IL-10 production in eyes from wild-type mice but was impaired in both TLR2- and TLR4-deficient mice, indicating that HSP70-TLR2/TLR4 axis plays an immunomodulatory role in subretinal fibrosis. Thus, these results suggest that HSP70-TLR2/TLR4 axis is a new therapeutic target for subretinal fibrosis due to prognostic CNV.